Role of Digital Financial Literacy and Digital Financial Behavior on Financial Well-being in Indonesia - Dewi, Cynthia Sari; Putri, Apriliana; Situmorang, Sangaviery Loucas (West Science Business and Management, 2024)
In the current digital financial era, this research explores the important and relevant impact of the lack of welfare of Indonesian society in facing digital financial transformation. With the aim of improving people's financial welfare, this research focuses on digital financial literacy and digital financial behavior. Using the Theory of Planned Behavior (TPB) from a financial perspective, this research seeks to provide an in-depth understanding of how digital financial literacy and digital financial behavior can help improve people's financial welfare. This research uses a quantitative approach by distributing questionnaires to workers in JABODETABEK. This research model uses Partial Least Square - Structural Equation Modeling (PLS-SEM) via the SmartPLS application. It is hoped that the research results can help the government, practitioners or policy makers in improving the financial welfare of the Indonesian people. The findings in this study show that workers in the JABODETABEK area that DFL influences DFB and FWB FS. Then DFB influences FWB FS. However, DFL has no effect on FWB FA and DFB FA.